Dated Phylogeny of Banisteriopsis (Malpighiaceae) Suggests an Ancient Colonization of the Cerrado and No Evidence of Human Manipulation in the Origin of B. caapi - Thais A. C. Santos; Bruno S. Amorim; Jefferson R. Maciel; Cassiano A. D. Welker; Scheila Cristina Biazatti; Regina C. Oliveira (Plants)
Banisteriopsis is a genus in the Malpighiaceae family with 61 species, notable for including ritualistic taxa such as B. caapi (Spruce ex Griseb.) C.V. Morton, one of the main components of Ayahuasca tea. We analyzed 38 Banisteriopsis species, representing more than 60% of the genus, to investigate its geographical origin, diversification period, and colonization routes in the Neotropics. Plastid genes (matK, ndhF, and rbcL) and nuclear regions (ETS, ITS, and PHYC) were used in our analyses. Divergence time analyses were performed using Bayesian inference with a relaxed molecular clock and ancestral area reconstruction. Our results show that Banisteriopsis originated in the Miocene approximately 22 million years ago, and its diversification coincides with the expansion of dry areas in South America. Banisteriopsis began colonizing the Cerrado earlier than most other plants, and the history of the genus reveals that the biome served as a source of species for Neotropical rainforests. Our results also indicate a probable ancient origin for B. caapi, with no evidence of human manipulation in its diversification, and they reinforce archaeological evidence of a millennia-old exchange of uses among Amazonian peoples.